2005
DOI: 10.1161/circulationaha.105.555573
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Body Mass and Body Composition on Circulating Levels of Natriuretic Peptides

Abstract: Background-The association between higher body mass index (BMI) and lower B-type natriuretic peptide (BNP) level is thought to be mediated by expression of the natriuretic peptide clearance receptor (NPR-C) in adipose tissue. To explore this association, we tested 2 hypotheses: (1) that N-terminal (NT)-proBNP, which is not believed to bind NPR-C, would not be associated with BMI and (2) that lower BNP would be more closely associated with fat mass than with lean mass. Methods and Results-Measurements of BNP, N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

20
296
9
10

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 386 publications
(335 citation statements)
references
References 17 publications
20
296
9
10
Order By: Relevance
“…In the abovementioned large-scale study, diabetes was another condition found to be in association with low plasma NP levels and the negative effects of obesity and diabetes on NP levels were reported to be additive. 4 The results of the study conducted by Das et al 1 was comparable with those of Wang et al 4 such that the subjects with lower NT-proBNP levels were less likely to have hypertension. On the contrary, diabetes was found to be a lowering factor for this molecule.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…In the abovementioned large-scale study, diabetes was another condition found to be in association with low plasma NP levels and the negative effects of obesity and diabetes on NP levels were reported to be additive. 4 The results of the study conducted by Das et al 1 was comparable with those of Wang et al 4 such that the subjects with lower NT-proBNP levels were less likely to have hypertension. On the contrary, diabetes was found to be a lowering factor for this molecule.…”
Section: Discussionsupporting
confidence: 59%
“…[1][2][3] In several studies, plasma ANP and BNP concentrations have been found to be decreased in obese subjects. [4][5][6][7] Additionally, an increase in natriuretic peptides (NPs) has been reported to parallel an increase in blood pressure.…”
Section: Introductionmentioning
confidence: 99%
“…14 An inverse association between body mass index (BMI) and NP levels has been consistently documented. 15 -17 Data from the Dallas Heart Study demonstrated an inverse association between lean mass, but not fat mass, with BNP and NT-proBNP levels (Figure 1), 18 an effect that appears to be mediated through a suppressive effect of androgens on NP synthesis. 19 This finding may be particularly important in the elderly, given the known reduction in lean mass/adipose tissue ratio and testosterone that occurs with aging 18 : lower lean mass and testosterone may contribute to age-associated increases in NP levels.…”
Section: Impact Of Aging-related Factors On Npsmentioning
confidence: 98%
“…Median levels of NT‐proBNP were >5500 pg/mL lower in patients with Class III obesity as compared with nonobese patients. Multiple analyses have reported similar findings 7, 8, 18. Mechanisms may include increased clearance of natriuretic peptides attributed to enzymes found in adipocytes and elevated glomerular filtration rates in the obese patient 19.…”
Section: Discussionmentioning
confidence: 75%
“…BNP and/or NT‐proBNP levels correlate with HF diagnosis, severity, and mortality 4, 5. However, obesity may be associated with lower circulating levels of BNP and/or NT‐proBNP 6, 7, 8, 9. Thus, the prognostic utility of NT‐proBNP may differ between obese and nonobese patients, though this has not been well characterized in patients with acute HF.…”
Section: Introductionmentioning
confidence: 99%